Hubungan Nilai Trombosit dan Hematokrit dengan Kegagalan Arteriovenous Fistula pada Pasien Gagal Ginjal - Satria, Muhammad; Rustam, Raflis; Rivaldy, Vendry (Politeknik Kesehatan Tanjung Karang, 2020)
Hemodialysis is a treatment for kidney failure that uses a machine to send the patient's blood through a filter. Arteriovenous fistulas (AVF) and arteriovenous grafts are vascular access that is designed for long-term use. In the world, the number of patients with end-stage chronic kidney failure (CRF) which requires hemodialysis is increasing. However, almost 50% of arteriovenous fistulas can never be used for hemodialysis, and if they can be used, 25% will experience failure after 2 years. Many factors make the AVF failure, between the injury of the endothelial wall or the hypercoagulation. This study uses a cross-sectional retrospective design. Data is taken from the medical record status of patients with chronic kidney failure in RSUP Dr. M.Djamil Padang from January 2017-December 2019. Data were analyzed by Chi-square and Fisher test. From a sample of 33 people, patients obtained hematocrit values <33%, 33-36%,> 36% failure of AVF as many as 8, 2, and 4 people. While the platelet values <150,000,150,000-400,000 and 400,000 obtained AVF failures were 0.9 and 5 people. There was no relationship of platelet values with AVF failure in hemodialysis patients with p-value=0,323. There was a correlation between hematocrit values and AVF failure in hemodialysis patients with p-value=0,003.